2012
DOI: 10.1021/nl3040948
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Strong Coupling in Silver Nanoparticle Arrays Using Photochromic Molecules

Abstract: In this Letter, we demonstrate a reversible strong coupling regime between a dipolar surface plasmon resonance and a molecular excited state. This reversible state is experimentally observed on silver nanoparticle arrays embedded in a polymer film containing photochromic molecules. Extinction measurements reveal a clear Rabi splitting of 294 meV, corresponding to ~13% of the molecular transition energy. We derived an analytical model to confirm our observations, and we emphasize the importance of spectrally ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
111
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 18 publications
3
111
0
1
Order By: Relevance
“…6c). Thereafter, a molecular plasmonic switch driven by photochemical and thermal stimuli was also demonstrated by Baudrion and co-workers [165]. These authors showed that when ultraviolet radiation was applied to spiropyran (SPy), a photochromic molecule, the SPy form transitioned to the merocyanine form.…”
Section: Plasmonic-molecular Resonance Couplingmentioning
confidence: 88%
See 1 more Smart Citation
“…6c). Thereafter, a molecular plasmonic switch driven by photochemical and thermal stimuli was also demonstrated by Baudrion and co-workers [165]. These authors showed that when ultraviolet radiation was applied to spiropyran (SPy), a photochromic molecule, the SPy form transitioned to the merocyanine form.…”
Section: Plasmonic-molecular Resonance Couplingmentioning
confidence: 88%
“…In addition to the demonstration of plasmonic-molecular resonance coupling for small-molecule detection, coupling of this kind has been used for the monitoring of reversible switching of molecules from non-resonant to resonant states, so-called molecular plasmonic switching [164][165][166][167][168][169][170]. For instance, chemically driven redox-controllable bistable [2]rotaxane was reported for the construction of a molecular plasmonic switch (Fig.…”
Section: Plasmonic-molecular Resonance Couplingmentioning
confidence: 99%
“…Specifically, plasmonic cavities are specially designed metallic nanostructures, in which collective oscillation of conduction electrons, known as localized surface plasmons, can be excited upon illumination. The interaction between plasmonic resonances and nearby atomic or molecular excitons gives rise to so called plexcitonic coupling [16].For convenience of measurements, previous experiments exploring plexcitonic coupling were primarily based on ensemble metallic nanostructures, including arrays of nanovoids [17,18] or nanoparticles (NPs) [19][20][21][22][23] and nanocrystals in solution [16,[24][25][26]. Recently several groups have 3 moved to a much smaller scale, investigating strong interaction of molecular excitons with individual plasmonic resonators, such as metallic nanospheres [27,28], nanorods [29][30][31], nanoprisms [15] and nanodisk dimers [13].…”
mentioning
confidence: 99%
“…A reversible strong coupling was found between dipolar surface plasmon resonance of Ag nanoparticles and the electronic transition of spiropyran molecules in a polymer binder [115]. The coupling strength depended on the spectral position of the surface plasmon resonance and the conformational molecular state.…”
Section: Scheme 78 Scheme 79mentioning
confidence: 95%